Hydrology, water quality and trophic state of Pergau Reservoir, Kelantan, Malaysia - Zullyadini A. Rahaman (Tanjung Malim, 2023)
Hydrology, water quality and trophic state of Pergau Reservoir, Kelantan, Malaysia by Zullyadini A. Rahaman